Regulation of mesenchymal stem cell-derived exosomes on helper T cells in periodontitis - WEN Yuqi, GUO Shujuan, DING Yi (口腔疾病防治)
T helper cells (Th cells) play an important role in periodontitis. During the progression of periodontitis, the levels of pro-inflammatory cytokines such as INF-γ and IL-17, which are produced by Th1 and Th17 cells, are elevated, while the levels of anti-inflammatory cytokines such as IL-4 and TGF-β, which are secreted by Th2 cells and regulatory T cells (Tregs), are diminished. Interventions using mesenchymal stem cells (MSCs) or their exosomes can alter the dynamics of helper T cell populations and their associated cytokine profiles, thereby mitigating the bone loss associated with periodontitis or even promoting bone regeneration. Mesenchymal stem cell-derived exosomes (MSC-exos) have been shown to directly modulate Th cell activity through the proteins and microRNAs they transport. Recent studies indicate that MSC-exos carry immune-suppressive protein molecules: PD-L1 and IDO contribute to regulating the balance between Th17 and Tregs; TGF-β inhibits the proliferation of T lymphocytes while facilitating differentiation into Tregs by sustaining forkhead box protein O3 (FOXP3) and Smad expression; and CD73 catalyzes the conversion of monophosphate adenosine into adenosine, which interacts with A2A receptors on Th1 cells to induce apoptosis in Th1 cells. In addition, microRNAs exhibit immunoregulatory functions: periodontal ligament stem cell-derived exosomes contain miRNA-155-5p, which targets sirtuin-1 to suppress Th17 cell differentiation. Furthermore, evidence in rat models of periodontitis suggests that these exosomes may also carry miR-205-5p targeting XBP1 to restore the balance between Th17 and Tregs. Dental pulp stem cell-derived exosomes reestablish this balance via the miR-1246/Nfat5 axis. Bone marrow mesenchymal stem cell-derived exosomes harbor miR-1246, which targets ACE2 to promote differentiation towards Tregs. Moreover, MSC-exos can indirectly enhance the differentiation of Tregs through interactions with other immune entities, such as antigen-presenting cells or macrophages. This article reviews the changes and roles of helper T cells in periodontitis, as well as the regulatory role of exosomes on helper T cells, hoping to provide new ideas for immunotherapy in the treatment of periodontitis.